Towards interoperable recordkeeping systems: A meta-model for recordkeeping metadata. (17th July 2017) - Rolan, Gregory
Abstract : Purpose: The purpose of this paper is to introduce an infrastructural approach to metadata modelling and a generalised meta-model for recordkeeping metadata. This meta-model is an attempt to support interoperability between disparate systems, and particularly, between sets of ostensibly incommensurate record documentation. Design/methodology/approach: The investigation used a reflective design-science investigation comprising interviews adaptive literature review, creation of conceptual models and the design and instantiation of a proof-of-concept system. Findings: The investigation confirms that recordkeeping interoperability between disparate ontologies is achievable through a meta-model approach. In particular, the meta-model carefully defines relationships between entities with specific semantics that enable the development of interoperable domain schemas. Practical implications: A meta-model for recordkeeping metadata facilitates the development of recordkeeping systems that possess interoperability-by-design. Social implications: Recordkeeping systems that conform to the meta-model can, therefore, transcend the immediate transactional context and support participatory recordkeeping in terms of a plurality of stakeholder world views and agency in records. Originality/value: This paper is one of the few reporting design-science approaches to recordkeeping informatics and one that has used a meta-model approach for recordkeeping metadata design. In contrast to most empirically determined metadata schemas, the top-down design approach has produced a schema from a wide variety of ontological sources.